Pendampingan Pengelolaan Perpustakaan Sekolah Sebagai Sumber Belajar Siswa di SDI Malafai - Itu, Maria Alexandra; Wau, Maria Patrisia; Longa, Viviana Meo; Ngadha, Christina; Dhoka, Fransiska Angelina (Abdimas Indonesian Journal, 2025)
Library management assistance at SDI Malafai aims to increase the role of libraries as a source of student learning. This activity began with observations and interviews to identify problems, such as limited space, lack of book collections, and lack of literacy programs. Assistance is carried out in four stages, namely planning, preparation, implementation, and evaluation. The results show that there is an improvement in library governance, including room arrangement, book procurement, and SOP arrangements. Obstacles such as the lack of special staff and inadequate facilities remain challenges, but it is recommended that there is training, appointment of officers, and cooperation with external parties to improve the quality of the library in the future.